How ChatGPT transformed teachers: the role of basic psychological needs in enhancing digital competence - Zhou, Jinshan; Shen, Lihan; Chen, Weibang (Frontiers in Psychology, 2024)
ChatGPT is rapidly and significantly impacting various industries, including the education sector. This study thus examined the influence of ChatGPT on teachers' digital competence (TDC) and explored the mediating role of basic psychological needs satisfaction, as outlined in self-determination theory. Data from 632 teachers were collected via a questionnaire distributed via Questionnaire Star. SmartPLS 4.0 was used to construct a structural equation model because of its robustness in handling complex models. These findings suggest that ChatGPT has a substantial positive effect on TDC. This improvement is attributed primarily to the satisfaction of competence and relatedness needs. However, autonomy did not significantly influence TDC. The findings emphasize the crucial importance of AI technologies in contemporary education, indicating that ChatGPT can serve as a potent instrument for augmenting TDC.